PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEREDARAN OBAT IMPOR YANG TIDAK MEMILIKI IZIN EDAR OLEH PENYIDIK PEGAWAI NEGERI SIPIL BALAI BESAR PENGAWAS OBAT DAN MAKANAN DI PEKANBARU - SYAFRINA MAISUSRI; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Medicine as a very important component for supporting health treatment for society. Distribute of medicine in society must have license, for production of medicine in of the country and import medicine, that gived by Badan POM (The National Agency of Drug and Food Control). Article 106 clause (1) law Number 36 of 2009 on Health, the preparation of pharmaceutical and health equipments can only be released after obtaining the marketing authorization. So, preparation of pharmaceutical can distribution in Indonesia if has been valuated throught mechanism medicine registration for get license. Illegal import medicine distribution will endanger its consumers’ health and safety because there is no safety, efficacy and quality guarantee of Badan POM.In reality, there are many illegal import medicine distribution cases the pharmacy in Pekanbaru. For example in Apotek Cempaka, Balai Besar POM Pekanbaru (Provincial office of Drug and Food Control in Pekanbaru) to found 58 items illegal import medicine, there are tebonin forte, lescol xl, camazol, navamin and so many import medicine that not yet have license. This show that law enforcement for illegal import medicine distribution in Pekanbaru conducted by Balai Besar POM Pekanbaru is not optimal.Keyword: Law enforcement, import medicine distribution lisence.